Editorial - Sarojini Nadar; Fatima Seedat (African Journal of Gender and Religion (AJGR))
In June 2016 the South African Commission on Gender Equality declared that a local KwaZulu-Natal municipality’s scheme of “bursaries for virgins” was unlawful, unconstitutional, and discriminatory. The findings and recommendations of the report were celebrated by gender activists who welcomed the recognition of the CGE that this scheme was marked by culturally patriarchal ideals of women’s bodies. Significant within the celebrations of the ruling, was little evidence of deep and thoughtful engagement with the tensions between provisions by the constitution of South Africa for cultural and religious freedom and women’s bodily autonomy. Moreover, the ruling brought up for introspection an interrogation of the ways in which femininity and masculinity are conceptualized within religious and cultural domains. This and other contemporary case studies within South Africa and beyond, highlight the need for continuous and sustained theoretical and philosophical engagement on the intersections of gender, religion and culture that is firmly rooted within an advocacy paradigm.